EFEKTIFITAS REHABILITASI PECANDU NARKOTIKA MELALUI TERAPI ISLAMI DI BADAN NARKOTIKA NASIONAL (BNN) BANDA ACEH - Nurdin Bakri; Barmawi Barmawi (State Islamic University (UIN) Ar-Raniry, 2017)
The purpose of this research is to improve the understanding, appreciation and use of Islamic values in all aspects of life. This discussion entitled